Implementation and Perceptions of Learning Reading, Writing, and Speaking Skills Through the Saiwa Method for Japanese Language Education Students - Manuhutu, Athalia Agave Arneta; Saragih , Febi Ariani (Journal of Agriprecision & Social Impact, 2025)
This study aims to analyze the implementation and perceptions of applying the Saiwa method in learning Joukyuu dokkai 1 for Japanese Language Education students at Brawijaya University during the 2020/2021 academic year. The method used is descriptive qualitative using observation sheets (indirect observation) to collect learning documentation data and questionnaires to explore student responses. The results showed that the implementation of Joukyuu dokkai 1 learning through the Saiwa method gave good results. The responses from students to this learning were mostly positive, with the majority of respondents stating that the Saiwa method of learning Joukyuu dokkai 1, which involves reading, writing, and speaking skills, can be felt to be beneficial.This research is also beneficial for Japanese language instructors in teaching reading courses, as it encourages the use of engaging methods over conventional, monotonous ones, thereby making learning more meaningful.